Restoring drinking water acceptance following a waterborne disease outbreak: the role of trust, risk perception, and communication. Issue 9 (4th August 2013) - Bratanova, Boyka; Morrison, Greg; Fife‐Schaw, Chris; Chenoweth, Jonathan; Mangold, Mikael
Abstract: Although research shows that acceptance, trust, and risk perception are often related, little is known about the underlying patterns of causality among the three constructs. In the context of a waterborne disease outbreak, we explored via zero‐order/partial correlation analysis whether acceptance predicts both trust and risk perception (associationist model), or whether trust influences risk perception and acceptance (causal chain model). The results supported the causal chain model suggesting a causal role for trust. A subsequent path analysis confirmed that the effect of trust on acceptance is fully mediated by risk perception. It also revealed that trust is positively predicted by prior institutional trust and communication with the public. Implications of the findings for response strategies to contamination events are discussed.